Good Handling Socialization of Mud Crab (Karaka) Catches In Fanamo And Omawita Villages Mimika Timur Jauh District: Sosialisasi Penanganan Hasil Tangkapan Kepiting Bakau (Karaka) Yang Baik Di Kampung Fanamo Dan Omawita, Distrik Mimika Timur Jauh - Yundy Hafizrianda; Ida Ayu Purba; Transna Putra Urip; Pisi Bethania Titalessy; Agustina Ester Antoh (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Mud crab (Scylla spp.), locally known as karaka, is a high-value fisheries commodity that supports the livelihoods of coastal communities in Mimika Regency, particularly in Fanamo and Omawita Villages, East Mimika District. However, inadequate post-harvest handling practices have resulted in high mortality rates, reduced product quality, and low market prices received by fishers. This community service program aimed to improve fishers’ knowledge and skills in proper mud crab handling based on Better Management Practices (BMP). A participatory and qualitative descriptive approach was applied through socialization sessions, focus group discussions, technical demonstrations, and hands-on practice. The results indicate a significant improvement in participants’ understanding of quality standards, appropriate storage and transportation techniques, and common handling errors. Implementation of BMP principles reduced crab mortality rates from an estimated 15–20% to below 5%, leading to substantial potential income gains for fishers. Beyond economic benefits, the activity also enhanced awareness of sustainable mud crab management and the importance of conserving mangrove ecosystems. Overall, this program contributed to strengthening fishers’ capacity, improving their bargaining position within the supply chain, and supporting more sustainable coastal fisheries management in Mimika Regency.